STRATEGI PEMASARAN PRODUK SAMBAL SAGELA UNTUK MENINGKATKAN VOLUME PENJUALAN PADA IKM BILAL MEKAR SNACK (IKM-BMS) DI KELURAHAN BULOTADA'A KOTA GORONTALO - Pontoh, Siti Hajar Mirantia; Bempah, Irwan; Saleh, Yanti (Agrinesia: Jurnal Ilmiah Agribisnis, 2023)
This marketing strategy aims to (1) Identify the Bilal Mekar Snack IKM institutions in Gorontalo City (2) Analyze alternative marketing strategies that can be applied to Bilal Mekar Snack IKM in order to increase sales volume of Sagela Sambal. The research used in this study is descriptive qualitative research with data analysis techniques SWOT data analysis. The research results show that 1). The factors that exist in IKM-BMS consist of internal factors in the form of strengths and weaknesses that affect the continuity of IKM-BMS in facing very tight market competition and external factors in the form of opportunities and threats. ) affect the sustainability of IKM-BMS. 2). Based on the results of the IFE matrix analysis for strengths and weaknesses, the total score was above the average of 3.0 with a total score of 5.827. This identifies the position of IKM-BMS as very strong. In other words, IKM-BMS can take advantage of the strengths that exist in IKM-BMS to minimize the weaknesses that exist in IKM-BMS. As for the results of the EFE factor analysis for opportunities and threats, a score of 5.806 was obtained, this indicates that the IKM-BMS is above the average of 3.0. Score of 5.806. This shows that IKM-BMS responds strongly to every strength and opportunity that exists.Keywords: Marketing Strategy and Sambal Sagel.